Peanut (Arachis hypogaea) response to weed and disease management in northern Ghana. Issue 3 (3rd July 2018) - Abudulai, Mumuni; Naab, Jesse; Seini, Shaibu Seidu; Dzomeku, Israel; Boote, Kenneth; Brandenburg, Rick; Jordan, David
ABSTRACT: Weeds and diseases can reduce peanut ( Arachis hypogaea L.) yield or increase cost of production to maintain acceptable yield. While herbicides and fungicides have limited availability in many areas of Ghana and currently are too expensive for resource-poor farmers, control by these pesticides can have a major positive impact on peanut yield. Field experiments were conducted during the rainy seasons of 2009 and 2010 in northern Ghana to determine the effects of herbicide and hand weeding in combination with fungicides on pest management and peanut yield. Peanut pod yield was often more highly correlated with disease severity and canopy defoliation resulting from early leaf spot (caused by Cercospora arachidicola Hori) and late leaf spot (caused by Cercosporidium personatum (Berk. & M.A. Curtis) Deighton) than weed biomass. In some instances, less disease and canopy defoliation were observed when weeds were not controlled effectively compared with increased weed management through hand weeding or herbicide. Two hand weedings or applying pendimethalin preemergence with one hand weeding in combination with 4 applications of triadimefon and chlorothalonil resulted in the lowest weed density and canopy defoliation and often resulted in the highest peanut yield.